Vulnerability zoning of earthquake disaster of Palu - H Rusydi; Rustan Effendi; Rahmawati Rahmawati (International Journal of Science and Applied Science: Conference Series, 2017)
Palu is the area traversed by Palu-Koro faults and some small faults arround, which causes the frequent occurrence of earthquakes in Palu. Therefore, this study aims to determine the vulnerability of earthquake zone. Determination of this zona is one way to reduce the risk of earthquake disaster. This study used two methods, they are are descriptive and overlay weighted sum. For the overlay of data processing method using GIS application. The result of the study showed 45 district in Palu, 12 district located in low vulnerability zone, 11 district located in moderate vulnerability zone and 22 district located in high vulnerability zone.